Stakeholder theory: A deliberative perspective. (4th September 2017) - Richter, Ulf Henning; Dow, Kevin E.
Abstract: Organizations routinely make choices when addressing conflicting stakes of their stakeholders. As stakeholder theory continues to mature, scholars continue to seek ways to make it more usable (and relevant), yet proponents continue to debate its legitimacy. Various scholarly attempts to ground stakeholder theory (empirically, instrumentally, or normatively) have not narrowed down this debate. We draw from the work of Juergen Habermas to theoretically advance stakeholder theory, and to provide practical examples to illustrate our approach. Specifically, we apply Habermas' language‐pragmatic approach (which places strong emphasis on dialogue, participation, and procedural justice) to extend stakeholder theory by advancing seven sets of normative axioms (10 axioms in total). We conclude that a deliberative approach, with its focus on the conditions of legitimation and deliberative democracy, has the potential to become a cornerstone of stakeholder theory. The need for global stakeholder discourse and its internalization in corporate structures and institutions is exemplified by a multitude of CSR and stakeholder initiatives that have mushroomed in response to global risk scenarios such as climate change, nuclear warfare, or terrorism. Further research may help to build a functioning global governance system in order to provide guidance for management in the 21st century.